TINGKAT PARTISIPASI PEMBUDIDAYA IKAN DALAM KEGIATAN PENYULUHAN PERIKANAN DI DESA PANORAGAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Markus Natan; Nurul Ovia Oktawati; Oon Darmansyah (2339-1324, 2020)
This research aimed to (1) Know the participation level of fish cultivator in fishery counseling activity in Panorangan Village Loa Kulu Sub-District Kutai Kertanegara District, (2) know the factors affecting the participation level of fish cultivator in fishery counseling activity in Panorangan Village Loa Kulu SubDistrict Kutai Kertanegara District.Sampling was done through census method. Meanwhile, the data analysis method used was analysis of likert scale and suparman formulation. The research result showed that the participation level of fish cultivator in fishery counseling activity in Panorangan Village Loa Kulu Sub-District Kutai Kertanegara District can be seen in terms of partial and accumulative, which is: partially, the participation level of fish cultivator in fishery counseling activity in Panorangan Village Loa Kulu Sub-District Kutai Kertanegara District was in medium category based on the participation indicator in which the awareness score is 15.2, the involvement score is 8.7, and the benefit score is 8.5. Furthermore, accumulatively, the participation level of fish cultivator in fishery counseling activity in Panorangan Village Loa Kulu Sub-District Kutai Kertanegara District was also in medium category with the score of 32.4. Factors affecting the participation level of fish cultivator in fishery counseling activity in Panorangan Village Loa Kulu Sub-District Kutai Kertanegara District is factor of fish cultivation experience, job, and area width.